Analgosedation in neonates: what we know and how we act - Allegaert K; Bellieni CV (Dove Medical Press, 2013)
Karel Allegaert,1,2 Carlo V Bellieni3 1Department of Development and Regeneration, 2KU Leuven and Neonatal Intensive Care Unit, University Hospitals Leuven, Belgium; 3Department of Pediatrics, Obstetrics and Reproduction Medicine, University of Siena, Siena, Italy Abstract: Inadequate pain management in neonatal life impairs the neurodevelopmental outcome. It alters pain thresholds, pain and stress-related behavior, and physiologic responses in later life. At the same time, there are emerging animal experimental and human epidemiologic data on the impact of analgosedatives on neuroapoptosis and impaired neurodevelopmental outcome. As a consequence, the management of neonatal pain is in search of a new equilibrium since these conflicting (undertreatment versus overtreatment) observations are the main drivers of its current management. Such tailoring includes new treatment modalities, and also more effective implementation strategies. The search for tailored nonpharmacologic (ie, less invasive techniques, preventive strategies, complementary techniques) and pharmacologic (eg, dexmedetomidine, intravenous acetaminophen, remifentanil) treatment modalities are discussed and reflect the increased knowledge on neonatal pain management. Despite this increasing knowledge (“toolbox”) regarding neonatal pain, there is still a major gap between knowledge (“what we know”) and practice (“how we act”). Consequently, more research activity on methods for effective implementation of the available knowledge is needed. Illustrations of effective approaches, eg, the Evidence-Based Practice for Improving Quality (EPIQ) initiative, to bridge this gap are provided. This is followed by an intersubjective proposal on priorities for contemporary clinical management and a research agenda. Keywords: pain, newborn, prevention, guidelines